John Lydgate’s Guy of Warwick and Fifteenth-Century Emotions - Czarnowus, Anna (Studia Anglica Posnaniensia, 2021)
The article argues that John Lydgate’s Guy of Warwick is an innovative version of the Guy of Warwick legend as it emphasizes the feelings of its characters. Furthermore, it also openly intends to evoke emotions in its audience. The poem requires to be read in light of the newly emerged field of the history of medieval emotions since the social context of Lydgate’s Guy is more visible from this perspective. The poem offers an admixture of religious and secular feelings. As a result, the final scenes of bidding farewell to Guy by Felice and by the community have to be seen as related both to Guy as a hero and as a saint.